Profesionalisme Make Up Artist Pria di Surabaya - Widiyantari, Dwika Ramadhani; Faidah, Mutimmatul; Dwiyanti, Sri; Kecvara Pritasari, Octaverina (Jurnal Tata Rias, 2025)
Professionalism is an attitude that is carried out when carrying out a profession that is not based only on filling free time and pursuing hobbies alone. Professionalism can be interpreted as the knowledge that is possessed when carrying out a job. Every individual definitely wants success, whether success in terms of career, study, friendship, family, and others. The first step to success is to understand yourself and your qualities. Understanding yourself and your qualities is very important. So that we can understand ourselves and our qualities, we need to form a self-concept or what is known as self-concept. The objectives of this research are 1) to describe the professionalism of male make up artists. 2) to explain the self-concept of male make up artists. 3) Factors underlying the professionalism of male Make Up Artists. This research adoption descriptive qualitative approach which cover collection data, reduction data, presentation of data and conclusions. The respondents for this research consisted of 5 male makeup artists in Surabaya. This research method uses interviews, observation, and documentation. The results of the research that has been carried out are 1) From several informants who have been researched to gain professionalism, these informants do several things such as courses, beauty schools, and privately at several professionals as well 2) There are things that influence self-concept, namely self-image, self-ideal, self-esteem, self-role, and self-identity. There are also factors that influence self-concept which consist of self-appraisal, reaction and response of others, roles you take, reference groups. 3) Factors that influence the performance of this male Make Up Artist are the self-concept that has been formed since childhood and the surrounding circumstances.   Keywords: Profesionalism, Self Concept, Factor of Profesionalism, Make Up Artist.